Grid-tied PEMFC power conditioning system based on capacitor voltage thorough feedback procedure in a weak and harmonics-polluted network - Hosseinpour, Majid; Sabetfar, Tooraj; Shahparasti, Mahdi (John Wiley & Sons, 2024)
Proton exchange membrane fuel cells (PEMFC) have been noticed by researchers due to their high efficiency, low pollution, and high-power density in distributed generation systems. In this paper, an LCL-type grid-tied PEMFC fuel cell power conditioning system is evaluated in a harmonics-polluted low-voltage grid. The LCL-filters can lead to resonance and instability despite their capability to attenuate harmonics. In this research, a transformer has been used to connect the fuel cell inverter to the grid. The grid-side inductor of LCL-filter is realized by the leakage inductance of the transformer. In addition, for more effective resonance damping and attenuation of current ripples caused by the grid voltage harmonics, a capacitor voltage comprehensive feedback control has been designed and investigated. The comprehensive feedback control of the capacitor voltage contains proportional, first and second-order derivative terms. In the proposed control scheme, the capacitor-current-feedback is opposed by the capacitor voltage derivative term due to reverse loop gain, which leads to deleting both of these loop gains. As a result, there is no need to utilize a current sensor in this control method. Consequently, the proportional and second-order derivative terms of the capacitor voltage attenuate the LCL-filter resonance. A low-pass filter is also considered in the second-order derivative loop in the controllable frequency range to ensure system stability. The simulation results of the PEMFC power conditioning system in different conditions confirm the proper attenuation of LCL resonance of grid-tied inverter, high-quality current injection to the harmonics polluted grid, the suitable stability, and the appropriate dynamic response for the proposed system. Under the proposed control scheme, the fuel cell power conditioning system demonstrates satisfactory stability. Even when reducing the LCL filter values by 5%–20%, the system maintains its stability effectively. Moreover, the THD of the injected current into the grid, employing the proposed control strategy, has been successfully reduced to an impressive value of 1.97% in a weak and harmonical grid.
Keywords: capacitor voltage thorough feedback control; current harmonics attenuation; LCL-type grid-tied PEMFC; system stability; voltage; feedback; fi=Sähkötekniikka|en=Electrical Engineering|